Development of a chitosanase 3-like protein 1 assay kit and study of its application in patients with hepatocellular carcinoma - Min Liu; Yanru Qiu; Erfu Xie; Pu Qian; Shuxian Yang; Simin Zhao; Wenjun Yan; Xuan Huang; Shuang Han (BMC Biotechnology)
Abstract Objective The detection kit for plasma Chitinase-3-like Protein 1 was developed using the magnetic bead chemiluminescence method, in order to investigate the diagnostic value of DD, FDP, CHI3L1, AFP-L3 and PIVKA-II in hepatocellular carcinoma. Method The CHI3L1 detection kit was developed using the chemiluminescence method. The luminescence value obtained from the chemiluminescence analyzer was utilized for sensitive detection of CHI3L1, and the performance of the kit was evaluated accordingly. Moreover, this study enrolled 200 patients with hepatocellular carcinoma who were treated at the Oncology Department of the Affiliated Hospital of Jiangnan University between August 2022 and November 2023 as study subjects, while 100 healthy individuals undergoing physical examinations during the same period served as a control group. The plasma CHI3L1 levels in these subjects were measured using our institute’s developed kit. Simultaneously, DD, FDP, AFP-L3, and PIVKA-II levels were assessed in all subjects to investigate their relationship with general pathology in patients with hepatocellular carcinoma. Additionally, ROC curves were generated to evaluate both single and combined detections’ diagnostic efficacy for hepatocellular carcinoma. Result The serological index changes of DD, FDP, AFP-L3, PIVKA-II, and CHI3L1 were not associated with patient gender. The concentrations of AFP-L3 and PIVKA-II in the 45–59 age group were significantly higher than in other groups (P < 0.05). Additionally, DD, CHI3L1, and PIVKA-II levels were markedly elevated in patients with tumors > 5 cm, medium-to-high differentiation, nerve invasion, lymph node metastasis, or distant metastasis. In advanced liver cancer (stages III–IV), DD, FDP, and CHI3L1 concentrations were significantly higher than in early-stage patients (stages I–II). For single diagnostic analysis, the AUC for CHI3L1 was 0.923, while the combined AUC for all five indices was 0.961, indicating greater diagnostic value when used together. The CHI3L1 chemiluminescence detection kit had a minimum detection limit of 1.50 ng/mL, with precision and accuracy within 10%, and R > 0.99. Compared to a clinical reference kit, the correlation coefficient (R) was 0.994, meeting clinical performance evaluation criteria. Conclusion The CHI3L1 chemiluminescence kit developed meets clinical requirements. CHI3L1 can be used as an indicator for early screening of liver cancer, and the detection value of combined five indicators DD, FDP, AFP-L3, PIVKA-II and CHI3L1 is higher than that of single detection.